Effectiveness of Egg White Detoxe on Perineal Wound Healing in Post Labor Women - Idaningsih, Ayu; II, Yuyun Wahyu; Pratiwi, Nenden Meisandi; Hanib, Nurul Hazwani (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
One of the ways perineal wounds can be cured is with good nutrition, especially those high in protein. This study aimed to determine the effectiveness of boiled egg whites for perineal wound healing in postpartum mothers. This type of quantitative research uses a pre-experimental design with a one shot case study. The research was conducted at PMB Hj. Dewi Mulyati, S.ST in 2020-2021 with a population of postpartum women who experienced grade II perineal injuries and a sample of 15 people using an accidental sampling technique. The instrument uses an observation sheet and SOP for boiled egg whites. Univariate data analysis using distribution of central tendency in the form of mean, median, and standard deviation and bivariate data analysis using sample t-test showed the average perineal wound healing time after administration of boiled egg white. The results of this study were faster than in general, namely the healing time for perineal sutures lasted 6-10 days and no more than 14 days. It is hoped that health workers can practice and teach this technique to mothers to accelerate healing of perineal wounds and the results of this study can be an alternative innovation of natural treatment options.